The Role of High Technology In Training; Beyond Wilderness; Document Design from 1980 to 1989 - Debrah Jefferson; Tom Gentle; Carol Sanders Reiner (Journal of Applied Communications, 1991)
Reviews of "The Role of High Technology in Training," by Daniel Bissonnet; "Beyond Wilderness," Aperture; "Document Design from 1980 to 1989: Challenges That Remain," by Karen A. Schriver.